Scene in a sampler - Rushby, Pamela; Wallace-Mitchell, Jane (Macmillan Education Australia South Melbourne, Vic., 1997)
Scene in a Sampler is a charming exploration of storytelling through needlework, showcasing intricate designs that bring tales to life.